2021
DOI: 10.1080/14786419.2021.1925270
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and anti-inflammatory activities of Gallesia integrifolia (Phytolaccaceae) fruit essential oil

Abstract: The chemical composition of Gallesia integrifolia fruits essential oil was obtained by hydrodistillation using a modified Clevenger apparatus was investigated by gas chromatography coupled to mass spectrometry (GC/MS). In addition, the cytotoxicity activity against human tumor cell lines MCF-7 (breast adenocarcinoma), NCI-H460 (large cell lung carcinoma), HeLa (cervical carcinoma), and HepG2 (hepatocellular carcinoma), and non-tumor PLP2 (porcine liver primary cells) as well as the anti-inflammatory action was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 22 publications
3
8
0
2
Order By: Relevance
“…These values were only 5.71 and 8.57 times less active than the dexamethasone positive control (EC 50 = 6.3 µg/mL). Bortolucci et al [10] also reported the anti-inflammatory potential of the EO from fruits (EC 50 = 55 µg/mL) collected from the same specimen of G. integrifolia used in our study. The presence of lenthionine (9.27%) and dimethyl trisulfide (19.40%) was observed in the EO of the fruits (Table 3).…”
Section: Antiproliferative and Anti-inflammatory Activitysupporting
confidence: 74%
See 2 more Smart Citations
“…These values were only 5.71 and 8.57 times less active than the dexamethasone positive control (EC 50 = 6.3 µg/mL). Bortolucci et al [10] also reported the anti-inflammatory potential of the EO from fruits (EC 50 = 55 µg/mL) collected from the same specimen of G. integrifolia used in our study. The presence of lenthionine (9.27%) and dimethyl trisulfide (19.40%) was observed in the EO of the fruits (Table 3).…”
Section: Antiproliferative and Anti-inflammatory Activitysupporting
confidence: 74%
“…Studies conducted with essential oils and extracts from this species indicate anti-inflammatory, antiproliferative and antitumor [ 10 ], antifungal [ 8 , 11 ], acaricidal and larvicidal potential against Rhipicephalus microplus [ 12 , 13 ], larvicidal against Aedes aegypt [ 14 ], antiviral [ 15 ], antimycobacterial [ 9 ], and antiulcer [ 16 ] properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A G. integrifolia é reconhecida como sendo de grande importância para área medicinal como antiinflamatória e capacidade antimicrobiana (ARUNACHALAM et al, 2016;BORTOLUCCI et al, 2021), além disso apresenta atividade contra larvas do Aedes aegypti e carrapato bovino (DIAS et al, 2018;RAIMUNDO et al, 2021). O OE dos frutos de G. integrifolia tem alta atividade fungicida conforme os resultados publicados por Raimundo et al (2018) podendo servir como aplicações futuras na redução do uso de fungicidas sintéticos.…”
Section: Introductionunclassified
“…O OE dos frutos de G. integrifolia tem alta atividade fungicida conforme os resultados publicados por Raimundo et al (2018) podendo servir como aplicações futuras na redução do uso de fungicidas sintéticos. Estudos realizados por Bortolucci et al, (2021), utilizando o OE dos frutos, indicaram atividade antiinflamatória e células antitumoral.…”
Section: Introductionunclassified